Detecting mercury ions in water using a low-cost colorimetric sensor derived from immobilized silver nanoparticles on a paper substrate - Budlayan, Marco Laurence M (Archīum Ateneo, 2022)
The exceptional and specific reactivity of mercury ions (Hg2+) toward plasmonic silver nanoparticles (AgNPs) in aqueous media has motivated the need to develop innovative, low-cost, portable, and robust sensors to help address the detrimental effects of heavy metal contamination particularly in rural communities. In this paper, we present the plasmonic and colorimetric sensing of Hg2+ using a paper-based sensing material derived from thiamine-functionalized (ThAgNPs) that were immobilized on a commercial filter paper. Plasmonic AgNPs with a surface plasmon resonance peak at 420 nm and a size of about 21.3 nm were synthesized by a chemical reduction technique. Fourier transform infrared spectroscopy revealed the characteristic functional groups of thiamine in the spectra of AgNPs, thereby confirming the functionalization of AgNPs. The successful integration of ThAgNPs onto the Whatman filter paper (WFP) matrix was confirmed by the UV–vis and SEM-EDX results. An evident color change from yellowish to white was manifested by the fabricated WFP-ThAgNP sensor in the presence of Hg2+ with an appreciable detection of up to 0.5 µM using the naked eye. The colorimetric response of the sensor was also found to be selective towards Hg2+ after testing with different metal ions. Moreover, the response was consistent for tap, and creek water samples spiked with Hg2+. The results of this work provide a promising baseline technology for the development of an affordable, fast, portable, and reliable sensor that can be used for on-site detection and monitoring of Hg2+ levels in the water.